Effect of Polypropylene Fibre on Self- Compacting High-performance Concrete - Oesman, Mardiana; Herawati, Risma; Jauza, Zalfa Nuur (Universitas Islam Sultan Agung, 2024)
This study conducted tests on the design mixture of Polypropylene Fibre Reinforced Self-Compacting High-performance Concrete (PFRSCHPC) and Self-Compacting high-performance concrete (SCHPC) to determine the mechanical properties of the concrete, and the beams behaviour under bending loads. The composition of the mixtures of PFRSCHPC and SCHPC refer to Oesman, et al. (2022), which conducted research on UHPC (ultra-high-performance concrete) using natural sand and crushed stone through a 4.75mm sieve. PFRSCHPC and SCHPC compositions using Portland Slag Cement (PSC); 1% superplasticizer and 30% silica fume of the total binder; 1% Polypropylene fibre (PP); the ratio of sand to crushed stone 45%: 55%; and the w/b was 0.23. However, SCHPC as the control concrete mixture does not contain PP. The testing results of the PFRSCHPC showed compressive strength, tensile strength, flexural strength, and modulus of elasticity were 42.73 MPa; 4.33 MPa; 8.98 MPa; 45.51 GPa, respectively. When compared to SCHPC, PP has an influence in increasing tensile strength by 2.38 MPa (122.05%), flexural strength by 2.67 MPa (42.77%), and concrete elasticity modulus by 6.67 GPa (17.32%). However, 1% PP decreased compressive strength of PFRSCHPC, lower by 4.93 MPa (10.34%) compared to SCHPC. PFRSCHPC beam reached a peak load of 27.5 kN; initial stiffness of 5.32 kN/mm; ductility of 5.6; and toughness of 1606.08 kNm. PFRSCHPC beam with PP fibre content of 1% are able to increase 17.02% of peak load; 14.75% of ductility, and 113.91% of toughness.